Prescribing pattern of nutraceuticals in pediatric outpatient department at tertiary care teaching hospital - Kulkarni, Madhuri; Ambekar, Priyanka; Athawale, Siddharth (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Nutraceuticals use is increasing in a health-conscious society. Because of varying lifestyle diseases, people have changed their outlook towards nutraceuticals. The objective of the study was to study the prescription pattern of nutraceuticals by doctors in paediatric outpatient department of government medical college and hospital, Aurangabad, Maharashtra, India. Methods: This study was done between November 2018 to March 2019. Total of 156 patients were included in the study after obtaining written informed consent from parents of patients. The data was gathered, analysed and results were concluded. Results: Total 156 patients were prescribed nutraceuticals in paediatric outpatient department of which 51.92% female patients and 48.78% male patients received nutraceuticals. In this study, 62% patients received vitamins and 38% patients received vitamins and minerals. 67.31% patient receiving nutraceuticals were above the age of 6 years and 32.69% patients were under the age of 6 years. Among patients receiving nutraceuticals, B complex was received 55.77%. After that calcium lactate + vitamin D tablet were prescribed 21.80%. Ferrous sulfate + folic acid was received by 8.33% patients. Calcium carbonate + vitamin D3 were received by 7.69% patients. Folic acid tablet was received by 5.13% patients and poly-vitamin tablet by 1.28% patients. 100% prescriptions were prescribed in generic names. Conclusions: Nutraceuticals are being increasingly perceived as beneficial to health and are being continuously used in the treatment. The future of nutraceuticals is bright and can transform healthcare in a developing country like India.